Atypical colororation in the yellow-striped poisonous frog, Dendrobates truncatus (Cope, 1861), in the Colombian Magdalena river valley (2017)
ABSTRACT: Herein we report an atypical coloration in one individual of the yellow-striped poisonous frog, Dendrobates truncatus, in Colombian Magdalena middle valley. The adult individual presented leucism, a rare phenomenon occurs in nature or at very low frequencies.